2019
DOI: 10.1186/s41824-019-0066-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-FDG PET/CT in Diagnostic Oncology: a pictorial review

Abstract: Positron emission tomography/computed tomography (PET/CT) is currently one of the main imaging modalities for cancer patients worldwide. Fluorodeoxyglucose (FDG) PET/CT has earned its global recognition in the modern management of cancer patients and is rapidly becoming an important imaging modality for patients with cardiac, neurological, and infectious/inflammatory conditions. Despite its proven benefits, FDG has limitations in the assessment of several relevant tumours such as prostate cancer. Therefore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
(79 reference statements)
0
6
0
1
Order By: Relevance
“…The improved spatial resolution and sensitivity of PET scanners dedicated to breast (positron emission mammography) has allowed its clinical application in the study of primary tumors [ 79 , 80 ]. Numerous studies have shown that hybrid imaging with 18 F-FDG PET/CT provides information about the cellular glucose uptake, which is elevated in malignant lesions [ 81 , 82 , 83 , 84 ]. Jørgensen et al observed significantly reduced uptake of 18 F-FDG by tumor cells following nanoparticle-assisted photothermal therapy, indicating that it can be effectively used as a marker to assess treatment responses [ 85 ].…”
Section: Techniques For Diagnosis or Detection Of Breast Cancermentioning
confidence: 99%
“…The improved spatial resolution and sensitivity of PET scanners dedicated to breast (positron emission mammography) has allowed its clinical application in the study of primary tumors [ 79 , 80 ]. Numerous studies have shown that hybrid imaging with 18 F-FDG PET/CT provides information about the cellular glucose uptake, which is elevated in malignant lesions [ 81 , 82 , 83 , 84 ]. Jørgensen et al observed significantly reduced uptake of 18 F-FDG by tumor cells following nanoparticle-assisted photothermal therapy, indicating that it can be effectively used as a marker to assess treatment responses [ 85 ].…”
Section: Techniques For Diagnosis or Detection Of Breast Cancermentioning
confidence: 99%
“…One modality which has provided continuous innovation and therefore seen increasing use has been the positron emission tomography-computed tomography (PET-CT), mainly due to the development of new tracers in addition to the most prevalent 18 F-fluorodeoxyglucose ( 18 F-FDG) [ 1 ]. PET-CTs are nowadays recommended for a variety of clinical indications and have been shown to alter the management of oncology patients in many cases [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…When injected intravenously, this molecule can cross the blood-brain barrier to reach the dopaminergic neurons where it is used as a precursor of the neurotransmitter dopamine. In the field of nuclear oncology, the main clinical application of imaging with 18 F-DOPA is for the management of NETs and brain tumors [81,82]. On the basis of the knowledge that the amino acid DOPA is a precursor of melanin, 18 F-FDOPA PET has also been experimentally applied in melanoma patients in combination with 18 F-FDG.…”
Section: F-fluorodihydroxyphenylalanine ( 18 F-dopa)mentioning
confidence: 99%